Analisis Ketebalan Lapisan Sedimen Menggunakan Metode Horizontal to Vertical Spectral Ratio (HVSR) di Daerah Perbukitan Kecamatan Moramo - La Hamimu Hamimu; Laode Ihksan Juarzan; Nurul Irana Pathiasari (Program Studi Teknik Geofisika FITK UHO, 2024)
This research aims to determine value of the thickness of sediment layer (h) and the type of soil layer in the hilly area of Moramo District. This research uses microtremor data obtained from the TDL-303S Seismometer at 15 points with a distance between points of 400 m–800 m and shear wave velocity values up to a depth of 30 m (Vs30) obtained from USGS website data. Microtremor data were analyzed using HVSR method with Geopsy 3.4.2 software to obtain the dominant frequency value. The shear wave velocity value was extracted using ArcGis 10.8 software to determine Vs30 value at each measurement point. The f0 and VS30 values are used to determine the sediment layer thickness (h). The analysis results show that sediment layer thickness range between 5,03 m–47,43 m. The distribution map of sediment layer thickness values shows that research area with high sediment layer thickness values is located in a small part of Ulusena Village and Watu Porambaa Village. So, these two areas are at greater risk of experiencing damage due to earthquakes. The type of soil layers based on soil classification by Kanai (1983) are classified into 4 types of soil with the research area being dominated by Type I soil, where this type is tertiary or older rock consisting of hard gravelly sandstone. Type I is located in Wonua Jaya Village, the western and southern parts of Sumbersari Village, the eastern part of Pudaria Jaya Village, as well as small parts of Watu Porambaa and Ulusena Village.